Իշխանանիստ Սոթքը. պատմությունը և հուշարձանները - Գրիգորյան, Ավետիս (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Село Сотк находится на юго-востоке Гехаркуникской области Республики Армения. По версии историка Ст. Орбеляна, имя населенного пункта происходит от названия холодного ветра, дующего от горного перевала до Севана. Об армянской принадлежности средневекового Сотка свидетельствуют не только около двух десятков армянских средневековых письменных первоисточников, но и исторические памятники в окрестностях села – церкви, хачкары, армянские надписи. Соткская церковь принадлежала епархии моностыря Макеняц Армянской апостольской церкви, который был одним из древнейших орденов армянской церкви. Sotk village is located in the south-east of Gegharkunik province of the Republic of Armenia. According to Stepanos Orbelyan, the name of the settlement originates from the name of the cold wind blowing from the mountain pass to Sevan. The Armenian identity of medieval Sotk is evidenced not only by about two dozen Armenian medieval written sources, but also by historical monuments in the vicinity of the village – churches, khachkars, Armenian inscriptions. The church of Sotk belonged to the Diocese of the Makenyats Monastery of the Armenian Apostolic Church, which was one of the oldest orders of the Armenian Church.
Keywords: Քրիստոնեություն; Հուշարձաններ; Մշակույթ